Role of the Southern Ocean in the millennial scale climatic events of the last Glacial-Holocene transition : geochemical and micropaleontological approach - Haddam, Naoufel Abdeldjalyl (CCSD, 2016)
The last 22 kyr are marked by abrupt climatic events, non-synchronous between the southern and northern hemispheres. A see-saw mechanism of the polar temperatures, amplified by the deep oceanability to store and release a portion of atmospheric CO₂, depending on the intensity of the thermohaline circulation and the large upwellings along the southern divergence, has been proposed to explain these observations. The main aim of this thesis was to assess the role of the southern ocean during these millennial events, by studying 3 marine cores, retrieved along the Chilean margin, under the influence of oceanic fronts and the westerly winds. The reconstruction of the sea surface temperatures (SST) allowed tracing the evolution of the SST latitudinal gradient during the last 22 kyr, highlighting southward migrations of the Subtropical Front, especially during the deglaciation, marked by benthic and planktonic foraminifera faunal changes which can be interpreted as surface nutrients inputs increase, accompanied by an enrichment of the bottom water [O₂] in the bottom water. These events could be related to stronger upwellings at the southern divergence leading to an increase of the Antarctic intermediate waters ventilation. These changes occur during atmospheric CO₂ increases recorded in Antarctic ice cores, marking the deglaciation, and suggesting an intimate link between upwellings, the intensity of the intermediate waters ventilation, and deep ocean-atmosphere CO₂ transfers. Les derniers 22 kans sont marqués par des évènements climatiques rapides, non synchrones entre l‘hémisphère Sud et le Nord. Un mécanisme de bascule des températures polaires, amplifié par la capacité de l‘océan profond à stocker et à restituer une partie du CO₂ atmosphérique en fonction de l‘intensité de la circulation océanique et des upwellings le long de la divergence Australe, a été proposé pour expliquer ces évènements. L‘objectif principal de cette thèse a été de définir quel est le rôle de l‘Océan Austral durant ces variations ...